Effectiveness of the Cognitive-Behavioral Therapy on Weight Loss and Eating Behavior in Overweight Adolescents - Mina Farrokhi; Mohammadreza Seyrafi; Amin Rafieipour; Hasan Ahadi; Adis Kraskian Mujembari (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Nutrition education is a key component of health promotion programs and leads to the improvement of nutritional behaviors of adolescents. Understanding the stages of cognitive-behavioral therapy in eating behavior and weight loss in adolescents is important in terms of preventive care. Objectives: The purpose of this study was to determine the effectiveness of cognitive-behavioral therapy on eating behavior and weight loss in adolescents. Methods: The research method was semi-experimental with a pre-test and post-test design with a two-month follow-up with the control group. The statistical population consisted of all adolescents referred to counseling centers in Mashhad in autumn 2019; 30 of them were selected by convenience sampling method and were randomly divided into experimental, and control groups. The research questionnaires were demographic questionnaire, and eating behavior questionnaire. Data were analyzed using repeated variance analysis and SPSS.22 software. Results: The mean (SD) of age was 17.66 (4.49) years in the experimental group 59.7% and 17.01 (4.10) years in the control group. 65.9% in the experimental group and in the control group, 59.7% were girls and the mean (SD) of body mass index was 27.73 (1.34) in the experimental group and 27.32 (0.95) in the control group. The results showed that cognitive-behavioral therapy was effective in decreasing uncontrollable eating (P<0.01), emotional eating (P<0.01), weight loss (P<0.01), and increasing cognitive restraint (P<0.01) in adolescents. Conclusion: It is concluded that cognitive-behavioral therapy can be used as an effective treatment of weight loss and eating behavior in adolescents.